Does subgingival bacterial colonization differ between implants and teeth? A systematic review - Belén RETAMAL-VALDES; Marcio de Carvalho FORMIGA; Mariana Linhares ALMEIDA; Aretuza FRITOLI; Kadmo Azevedo FIGUEIREDO; Miriam WESTPHAL; Patricia GOMES; Magda FERES
Abstract The aim was of this study was to determine the current weight of evidence for the existence of specific differences between the microbiota of healthy teeth and healthy implants, or of teeth with periodontitis and implants with peri-implantitis. A systematic review was conducted according to the PRISMA statement. The MEDLINE, EMBASE and Cochrane databases were searched up to February 2018 for studies comparing microbiological data of biofilm samples collected from healthy teeth and implants or from teeth with periodontitis and implants with peri-implantitis. The weight of evidence was defined in three categories (strong, moderate and mild/some), according to the difference in number of studies showing statistically significantly higher counts and/or proportions and/or abundance and/or prevalence of microorganisms in health or in disease. Of the 132 articles identified, 8 were included. A wide range of microorganisms were present in different conditions but no microorganisms showed strong, moderate or mild/some evidence for a specific association with either teeth or implants. The results of this systematic review indicated that there is insufficient evidence in the literature to support specific differences between microorganisms colonizing teeth and implants, either in health or in disease.